РАСЧЕТ МАГНИТНОГО ПОЛЯ И МОМЕНТА МАГНИТОЭЛЕКТРИЧЕСКОЙ МАШИНЫ С ЯВНО ВЫРАЖЕННЫМИ ПОЛЮСАМИ НА СТАТОРЕ - Гребеников, В.В.; Прыймак, М.В. (Інститут електродинаміки НАН України, Київ, 2012)
Application of high-energy magnets can create electric motors that are significantly smaller amount of magnetic system in comparison with classical electrical machines. The questions of the theory and design of such electrical motors are still not sufficiently developed. The results of computer simulation of electrical motor magnetic system containing salient poles in the stator and coil-type windings are represented. Rotor is based on flat permanent magnets and ferromagnetic concentrators of magnetic fields. The results of calculation of magnetic field and torque depending from rotor position and various current density in stator windings are represented too. References 2, figures 2.